Developing Comprehensive Agricultural Supply Chain International Courses and their Key Market Driven Topics by Using Grey Relational Analysis (GRA) - Lee, Tzong-Ru; Jaroenwanit, Pensri; Lin, Yong-Shun (KKBS Journal of Business Administration and Accountancy, 2024)
This research aims to develop comprehensive agricultural supply chain international courses using a systematic approach. The study employs three key steps: 1) conducting a literature review to identify activities within the agricultural supply chain, 2) collecting data on market-driven topics from top-ranked agricultural universities, and 3) using Grey Relational Analysis (GRA) to determine key topics for each course. Data from agricultural professors and quantitative analysis are used to identify relevant themes. Respondents graded a statement on a Likert scale to rate each course topic's value. Teachers at Taiwan's top 7 agricultural schools from 30 world-class colleges were given questionnaires to collect data. Online surveys were distributed via Google Forms. Analysts utilized Grey Relational Analysis. This methodology ensures that the courses are aligned with current industry demands and educational gaps, providing relevant and up-to-date content for students. This analysis identified three to six market-driven subjects from each of the 17 comprehensive agriculture international courses. Educational institutions can utilize this article to build and improve international agriculture curricula. Building on the current study's conceptual foundations, especially the theoretically sound instrument for measuring agriculture supply chain international courses. Expand and explain this topic. This subject mix global agribusiness courses with transformative change for the first time. Nation advisors' innovation support is measured.